Assesstment of Panama as a humanitarian logistic hub / Juan Carlos Parada B., Niurka Pineda, Natalie Valenzuela ; asesora Dra. Ozlem Ergun - Parada Bolívar, Juan Carlos (Universidad Tecnológica de Panamá ; Georgia Institute of Technology ;, 2011)
This Capstone Project, Assessment of Panama as a Regional Humanitarian Logistics Hub, focused in to help the Humanitarian Organizations with presence in the Panama to understand their operations in the Region. The first step to accomplish this goal was understand the demand, to achieve this we gather historic data (1900 to 2010) for the Latin America and Caribbean Region from the Centre for Research on the Epidemiology of Disasters Database, data collected included the number of events and affected people for natural disasters such as Volcanoes, Earthquakes, Mass Movements, Droughts and Storms. After analyzing the data, we concluded that only data from 1966 to 2010 would be considered, due to the fact of low event registration in the beginning of the twenty century and a notable increase trend after 1965. Subsequently, we analyzed the data from 1966 to 2010, evaluating several forecasting models; double exponential smoothing was selected as our model and was applied to the data. Prior to this, the data was divided in sub- regions to evaluate the demand in a scenario that will lead to better response time. Our forecast predict that the designated regions, The Caribbean, Central America, South America and Southern Cone, will handle 26%, 26%, 37% and 11% respectively of the demand for 2011. Our next step consisted on design a network for the four sub-regions. This was done applying the Factor Rating Method; several factors were considered on this phase, such as the Logistics Performance Index, the Lead Time to resupply those countries, the Enabling Trade Index and the World Risk Index of Vulnerability. After applying this technique to all the countries in the Sub Regions, the results were as follows, for Central America, the warehouse should be located in Panama; for the Caribbean, should be located on Dominican Republic; for South America, Ecuador and for the Southern Cone, Chile. Afterwards, we decided to evaluate the Regional division, this was done compiling the transit time and air freight cost of from the each warehouse to the Southern Cone, South America and Central America Cities. Subsequently, we decided to change some countries of their assigned regions, testing a three warehouse scenario. Colombia was moved to Central America, Venezuela was moved to the Caribbean and the remaining countries in South America were merged with the Southern Cone. The outcome was evaluated in Demand and Network Configuration; the results of the one region of the forecast were more variable that in the previous setting, the network show two warehouses overcharged, due to this, we decided to maintain the four warehouse strategy over the one with three warehouses. The last part of the project was to conduct an analysis of Panama as a Humanitarian Hub, where we evaluated Panama versus Costa Rica from the Factor Rating results, for Central America. In that analysis Panama and Costa Rica where tied, so we used the Global Competiveness Report for 2010-2011 as well as the Logistics Performance Index for 2010 to make a comparison among this two countries. Despite they are neighboring countries Costa Rica in the future could become a rival for Panama as a Hub. Therefore Panama has been making strong investments to assure and strengthen their position as the Hub for the Americas.